Experimental study of radioprotective properties of lithium pyruvate in vitro - E. V. Plotnikov; M. V. Belousov; K. S. Brazovsky; M. S. Larkina; A. A. Artamonov; S. G. Stuchebrov; V. I. Chernov (Сибирский онкологический журнал, 2024)
Radiotoxicity is a serious problem for patients undergoing radiotherapy, so the search for new radioprotective drugs to mitigate its effects is highly relevant. Radioprotectors should have a number of properties, including direct antioxidant action, reduction of oxidative stress, ability to induce DNA repair or inhibit apoptosis, and at the same time not cause their own side effects. Antioxidants based on lithium salts look promising in terms of their properties. The aim of study was to study the radioprotective properties of lithium pyruvate in vitro. Material and Methods. Relatively radiosensitive blood mononuclear cells and relatively radioresistant fibroblasts of 3T3L1 line were used as biomodels for x-ray exposure. Cells were incubated and irradiated in 96-well plates. Lithium pyruvate was used at a final concentration of 1.2 mM. Cells were irradiated at a dose rate of 15 mGy/s in the absorbed-dose range from 0 to 5 Gy using an x-ray unit (anode voltage: 160 kV, average current: 3.5 mA). Cell viability was assessed by MTT test and resazurin test. The evaluation of cell death variants and the level of oxidative stress were determined by cytofluorimetric method. Results. The cytoprotective effect of lithium pyruvate was established. Cytoprotection was manifested in the increased cell survival and decreased oxidative stress level under lithium pyruvate after x-ray in a wide range of absorbed doses. Relatively high efficiency was shown in relation to blood mononuclear cells with an increase in the viable fraction by 5–7 % and a decrease in oxidative stress level during irradiation in the range of 1.0–3.0 Gy. Apoptosis was found to be the main mechanism of cell death after irradiation. Lithium pyruvate reduced the level of apoptosis in cell population under irradiation and chemically induced oxidative stress. Conclusion. Radioprotective effect of lithium pyruvate under x-ray irradiation in vitro has been shown. Reduction of oxidative stress under the action of pyruvate provides a pathogenetic basis for the potential use of this compound as a radioprotector, which requires further studies on in vivo models.